Mapping Of SMEs Digital Financial Transformation Research: A Bibliometric Analysis - Reza Widhar Pahlevi; Siti Resmi; Muhammad Roni Indarto; Tri Utomo Prasetyo (Akademi Akuntansi YKPN Yogyakarta, 2023)
With regard to keywords, research sites and topics, as well as the research methodologies, this study intends to carefully assess international scientific articles for SMEs Digital Financial Transformation research. Four key conclusions are presented in this study after reviewing 362 scientific papers. The main theme turns out to be the significance of digital financing for SMEs, which is followed by themes pertaining to digital transformation. Second, the most often utilized data sets are exploratory and case studies. Third, approximately the same number of studies have been conducted on the digital financial transformation of SMEs in developed and developing nations. Fourth, other study goals were suggested based on bibliometric methods with VOSviewer, which were divided into four groups and tested these themes to elaborate on theoretical and methodological elements. The future development of SMEs' digital financial transformation will be furthered by investigating this issue.